2020
DOI: 10.1364/optica.379228
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental investigation of silicon and silicon nitride platforms for phase-change photonic in-memory computing

Abstract: Advances in artificial intelligence have greatly increased demand for data-intensive computing. Integrated photonics is a promising approach to meet this demand in big-data processing due to its potential for wide bandwidth, high speed, low latency, and low-energy computing. Photonic computing using phase-change materials combines the benefits of integrated photonics and co-located data storage, which of late has evolved rapidly as an emerging area of interest. In spite of rapid advances of demonstrations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 53 publications
2
51
0
Order By: Relevance
“…For example, assuming a moderate datarate of 10 Gbits/sec and 4 WDM wavelengths in parallel per channel, the computing density will reach an upperbound value of 25 TOPS/mm 2 (Tera-operations per second per mm 2 ), which is significantly higher than that of digital electronic accelerators such as GPUs and tensor processing units (TPUs) 60 , 61 . Using silicon instead of silicon nitride can further reduce the device footprint to increase the computing density 62 . Besides MAC operation, the equally important computing processes of applying nonlinear functions and pooling can also be achieved optically by using elements such as nonlinear optical resonators, modulators, and amplifiers 27 , 28 , 63 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, assuming a moderate datarate of 10 Gbits/sec and 4 WDM wavelengths in parallel per channel, the computing density will reach an upperbound value of 25 TOPS/mm 2 (Tera-operations per second per mm 2 ), which is significantly higher than that of digital electronic accelerators such as GPUs and tensor processing units (TPUs) 60 , 61 . Using silicon instead of silicon nitride can further reduce the device footprint to increase the computing density 62 . Besides MAC operation, the equally important computing processes of applying nonlinear functions and pooling can also be achieved optically by using elements such as nonlinear optical resonators, modulators, and amplifiers 27 , 28 , 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Their work was originally addressed to the problem of SiN-based PICs having a fairly large footprint and offering relatively low contrast. It is worth noting that Li et al [89] actively compared the relative merits of Si and SiN platforms ( Figure. 9(b)) and found that Si is better in relation to its potential for integration with PCMs, its modulation speed and its footprint ( Figure. [87,88] was to introduce GST-clad microring resonators and directional couplers that could be tuned according to the state of the GST ( Figure. 9(e)). They also experimented with using two low loss PCMs, Sb 2 S 3 (SbS) and GeSe, with the electrical actuation of SbS being accomplished on-chip by using an external indium tin oxide (ITO) heater.…”
Section: On-chip Storage Memorymentioning
confidence: 99%
“…As mentioned above, basic tuning of the condition of the platform was accomplished by on the one hand achieving amorphization of the GST by means of a single short laser pulse (Figure 9(f)), on the other hand heating the GST to above its crystallization temperature by using a repeated sequence of short laser pulses or a single long pulse (Figure 9(g)). The heat dissipates more quickly in Si than for SiN when applying the same amount of optical power, so short, higher amplitude pulses tend to be more effective for PCMs [89]. By proceeding in this way, Fang et al [87,88] enabled highly controllable multi-level switching of the microrings by being able to shift the GST to different and intermediate states between its fully amorphous and fully crystalline states, each with different refractive properties ( Figure 10(a)).…”
Section: On-chip Storage Memorymentioning
confidence: 99%
See 2 more Smart Citations